Self-coloring of polymeric materials without coating/painting - Muhammad Yusoff Ab Rani (2018)
Structural coloration is a natural consequence of interactions between microscopically structured surface and visible light. The objective of this experiment is to achieve submicron wavelength of 0.5-1 µm atop polymer. By obtaining the submicron wavelength, structural coloration would be visible. There is a total of 4 sample material selected in this experiment. The materials are Poly (methyl methacrylate) (PMMA), PolyCarbonate (PC), Acrylonitrile Butadiene Styrene (ABS) and Polyurethane (PU). PMMA and PC are first cut into a dog bone shaped sample, ASTM D638. PC and ABS are in a filament form. A Differential Scanning Calorimetry (DSC) scan was conducted on the material to determine the glass transition temperature (Tg). Next, the materials are heated to its glass transition temperature (Tg) for tensile loading. The stretched material samples are then cut into smaller pieces. After which, the smaller samples are then exposed to acetone vapor for surface etching and finally reheated well above the glass transition temperature (Tg) for surface recovery to achieve the targeted submicron wavelength of 0.5-1 µm. The final analysis is conducted by analysing the sample’s 3D surface topography and its 2D Surface Profile using PLµ Confocal Image Profiler. Parameters that may affect the wavelength of the wrinkle includes the material selection, surface etching method and the selection solvent. These parameters can be further studied and researched upon to better achieve the submicron wavelength atop polymer for structural coloration.